HUBUNGAN PENGETAHUAN IBU DENGAN UPAYA PENCEGAHAN DEMAM TYPHOID PADA ANAK USIA SEKOLAH - Nopianti, Nopianti (Jurnal 'Aisyiyah Medika, 2019)
Background: Typhoid fever is a disease caused by bacterial infection of salmonella typhi. This disease is still an important health problem in many developing countries. In Indonesia, these cases are spread evenly throughout the province with the incidence in rural areas. The age of the affected patients in Indonesia is reported to be between 3-19 years. The incidence rate in Muhammadiyah Palembang hospital was 66 cases in 2017. Objective: This study aims to determine the relationship between maternal knowledge and efforts to prevent typhoid fever in school-age children. Methods: The method used is an analytical survey with a cross-sectional approach and techniques (total sampling), as for this study to study the dynamics of the correlation between risk factors and affect, by means of an observation approach or data collection at once (point time approach). Where this research was conducted at the Muhammadiyah Palembang Hospital and was carried out in January 2018 with a sample of 30 respondents, while bivariate analysis was to determine the relationship between spiritual intelligence and the quality of life of the elderly. Results: The results of the study of 30 respondents showed that the results of the bivariate analysis of knowledge had a value (p-0, 008), meaning that there was a significant relationship with the prevention of typhoid fever. It is hoped that knowing the relationship between maternal knowledge about Typhoid fever can prevent and overcome the occurrence of Typhoid fever. Suggestion: This study is expected for hospitals to improve the quality of service and provide information for Typhoid patients about the importance of preventing Typhoid disease. Keywords: Typhoid Fever, Knowledge, and Prevention Efforts